The Influence Of Earning Per Share (Eps), Dept To Equity Ratio (DER), And Company Age On Underpricing In Idx - Mulya Rizky Putri; Yeni Fitria; Bagus Setyadi; Imelda Deva; Sarah Haris; Nanda Ifandi (UNIVED Press, 2024)
This study analyzes whether the variables earnings per share (EPS), debt to equity ratio (DER), and Age Copies influence the underpricing of the Initial Public Offering (IPO). The theory related to underpricing is the signaling theory. The method used in this study is regression analysis. The results from this study show that only three variables, EPS, DER, and Age Companies, have a significant effect on underpricing. Because of the higher profitability, investors will be interested in buying or getting a substantial return on their participation. Simultaneously, no variables affected underpricing.